2021
DOI: 10.1002/hep4.1742
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Adenosine Triphosphate Reduction Through the Short‐Chain Fatty Acids–Peroxisome Proliferator‐Activated Receptor γ–Uncoupling Protein 2 Axis Alleviates Immune‐Mediated Acute Hepatitis in Inulin‐Supplemented Mice

Abstract: How liver tolerance is disrupted in immune-mediated liver injury is currently unclear. There is also insufficient information available regarding susceptibility, precipitation, escalation, and perpetuation of autoimmune hepatitis. To explore how dietary fiber influences hepatic damage, we applied the concanavalin A (ConA)-induced acute immune-mediated liver injury model in mice fed a diet supplemented with 6.8% inulin, a water-soluble fermentable fiber. Twelve hours after ConA administration, inulin-supplement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Researches showed that whole-grain dietary fber could improve the hepatic pathology and ameliorate the symptoms of diabetes by activating the IRS1/PI3K/AKT pathway in Db/ db mice [33]. Meanwhile, supplementing inulin rich in dietary fber could improve liver damage in mice with liver damage [34]. Whole grain dietary fber could reduce blood sugar by regulating the insulin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Researches showed that whole-grain dietary fber could improve the hepatic pathology and ameliorate the symptoms of diabetes by activating the IRS1/PI3K/AKT pathway in Db/ db mice [33]. Meanwhile, supplementing inulin rich in dietary fber could improve liver damage in mice with liver damage [34]. Whole grain dietary fber could reduce blood sugar by regulating the insulin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Other modulating approaches include prebiotics that can support the growth of certain beneficial taxa. Dietary fiber and inulin, both indigestible polysaccharides and fermented by the intestinal microbiota, ameliorated liver lesions in experimental AIH mice [71,72] …”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Dietary fiber and inulin, both indigestible polysaccharides and fermented by the intestinal microbiota, ameliorated liver lesions in experimental AIH mice. [ 71 , 72 ]…”
Section: Clinical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inulin is an indigestible, biodegradable natural functional dietary fiber and a natural prebiotic. Yamaguchi et al found that liver damage was significantly reduced histologically and serologically in mice fed inulin for 12h after ConA administration (66). In addition, antibiotics or specific vaccines can effectively inhibit the growth of enterococci and control the disease progression (59).…”
Section: Autoimmune Hepatitismentioning
confidence: 99%